Functional evaluation of ToxA promoter in Trichoderma reesei Rut-C30 - Ortiz, Gastón Ezequiel (2016)
In order to expand the collection of promoters studied in Trichoderma reesei Rut-C30, a functional study of the ToxA promoter was carried out by analysis of GFP expression in T. reesei Rut-C30. For this purpose, the binary pCBCT expression vector was employed to transform T. reesei Rut-C30. The transformants obtained were evaluated by means of fluorescence microscopy, fluorometry, dot blot and Western blot analysis. The low levels of cytoplasmic GFP protein in fungal hyphae suggest that ToxA promoter works as a weak constitutive promoter which can drive successfully the expression of heterologous proteins in T. reesei Rut-C30